The development of appropriate and consistent information for policy-making in post-conflict settings : lessons from the use of a household survey in Bosnia and Herzegovina - Black, Mary E. (Trinity College (Dublin, Ireland). Department of Public Health and Primary Care, 2012)
This study looks at the challenges in developing a national health information system (HIS) that is ‘fit for purpose’ to support policy-making in poorly resourced and postconflict settings. It examines how, and to what extent, a national household survey tool can contribute to the development of a sustainable HIS under the control of the national authorities. This includes getting data that is sufficiently accurate, timely, consistent between countries and across time and that is useful for national planning purposes. It also includes the improvement of national capacity to collect data, and the development of an integrated approach that is nationally relevant. This study aims to develop a better understanding of the role of UNICEF’s multiple indicator cluster survey (MICS) in providing information to support health policy in a post-conflict setting. It does this by a mixed-methods country case study using both qualitative and quantitative approaches. Bosnia and Herzegovina in 2000 was selected as an example of a post-conflict, resource-poor country facing typical challenges of a newly created administrative structure, gaps in population health data for child and maternal health, and a destroyed health information system. The complex national context included multiple international agencies with varying mandates and approaches to improving the national HIS. The governance and management model of the BiH MICS 2000 survey successfully addressed the fractured administrative structure in the country. A model for that enabled further national household surveys in BiH was created. The lessons learned in implementing the BiH MICS survey might be useful in other fragile states. The BiH MICS 2000 survey measured 32 internationally agreed indicators in the following health domains: education and literacy, access to clean water and sanitation, child nutrition, childhood immunization, the UNICEF/WHO global programme ‘Integrated Management of Childhood illness’, HIV/AIDS awareness, contraceptive prevalence, orphanhood, and child labour. A lack of socio-economic, ethnic or refugee/displaced information meant that population disparities, beyond urban and rural, could not be elicited from the data. The data provided substantial inputs into the four main national human development monitoring processes in close time proximity to the survey. They were: the National Report on Follow up to the World Summit for Children (2000), the National Action Plan for Children in Bosnia and Herzegovina 2002-2010 (2002), the Bosnia and Herzegovina Human Development Report/Millennium Development Goals 2003, and the Bosnia and Herzegovina Medium Term Development Strategy (2004). Comparison of the 32 indicators from 2000 with measures from 1990, 1995 and 2006 was limited by lack of comparable data from these three time points. A second BiH MICS survey, in 2006, provided the closest comparable indicators. The planned third BiH MICS survey in 2011 will create a unique national resource of information extending over 15-year period. The MICS data is widely presented, however there is currently no set of tools and guidelines for analysis of the MICS data over time. This study acknowledges the useful contribution by the BiH MICS survey indicators to international monitoring of child and maternal health, but not all indicators were relevant for a middle-income country, and the regional and national policy context of BiH was not sufficiently addressed. The survey draws attention to the need for a longer-term and more integrated approach to strengthening health information systems in post-conflict countries. Conducting a standalone household survey can produce data, but a national health information system requires a locally built and designed HIS architecture. Future MICS surveys and other data collection efforts should take into account the aspirations of BiH to join the European Union and the core indicator set being developed and maintained by EuroStat, the statistical office of the European Union. This study looks at the challenges in developing a national health information system (HIS) that is ‘fit for purpose’ to support policy-making in poorly resourced and postconflict settings. It examines how, and to what extent, a national household survey tool can contribute to the development of a sustainable HIS under the control of the national authorities. This includes getting data that is sufficiently accurate, timely, consistent between countries and across time and that is useful for national planning purposes. It also includes the improvement of national capacity to collect data, and the development of an integrated approach that is nationally relevant. This study aims to develop a better understanding of the role of UNICEF’s multiple indicator cluster survey (MICS) in providing information to support health policy in a post-conflict setting. It does this by a mixed-methods country case study using both qualitative and quantitative approaches. Bosnia and Herzegovina in 2000 was selected as an example of a post-conflict, resource-poor country facing typical challenges of a newly created administrative structure, gaps in population health data for child and maternal health, and a destroyed health information system. The complex national context included multiple international agencies with varying mandates and approaches to improving the national HIS. The governance and management model of the BiH MICS 2000 survey successfully addressed the fractured administrative structure in the country. A model for that enabled further national household surveys in BiH was created. The lessons learned in implementing the BiH MICS survey might be useful in other fragile states. The BiH MICS 2000 survey measured 32 internationally agreed indicators in the following health domains: education and literacy, access to clean water and sanitation, child nutrition, childhood immunization, the UNICEF/WHO global programme ‘Integrated Management of Childhood illness’, HIV/AIDS awareness, contraceptive prevalence, orphanhood, and child labour. A lack of socio-economic, ethnic or refugee/displaced information meant that population disparities, beyond urban and rural, could not be elicited from the data. The data provided substantial inputs into the four main national human development monitoring processes in close time proximity to the survey. They were: the National Report on Follow up to the World Summit for Children (2000), the National Action Plan for Children in Bosnia and Herzegovina 2002-2010 (2002), the Bosnia and Herzegovina Human Development Report/Millennium Development Goals 2003, and the Bosnia and Herzegovina Medium Term Development Strategy (2004). Comparison of the 32 indicators from 2000 with measures from 1990, 1995 and 2006 was limited by lack of comparable data from these three time points. A second BiH MICS survey, in 2006, provided the closest comparable indicators. The planned third BiH MICS survey in 2011 will create a unique national resource of information extending over 15-year period. The MICS data is widely presented, however there is currently no set of tools and guidelines for analysis of the MICS data over time. This study acknowledges the useful contribution by the BiH MICS survey indicators to international monitoring of child and maternal health, but not all indicators were relevant for a middle-income country, and the regional and national policy context of BiH was not sufficiently addressed. The survey draws attention to the need for a longer-term and more integrated approach to strengthening health information systems in post-conflict countries. Conducting a standalone household survey can produce data, but a national health information system requires a locally built and designed HIS architecture. Future MICS surveys and other data collection efforts should take into account the aspirations of BiH to join the European Union and the core indicator set being developed and maintained by EuroStat, the statistical office of the European Union. This study looks at the challenges in developing a national health information system (HIS) that is ‘fit for purpose’ to support policy-making in poorly resourced and postconflict settings. It examines how, and to what extent, a national household survey tool can contribute to the development of a sustainable HIS under the control of the national authorities. This includes getting data that is sufficiently accurate, timely, consistent between countries and across time and that is useful for national planning purposes. It also includes the improvement of national capacity to collect data, and the development of an integrated approach that is nationally relevant. This study aims to develop a better understanding of the role of UNICEF’s multiple indicator cluster survey (MICS) in providing information to support health policy in a post-conflict setting. It does this by a mixed-methods country case study using both qualitative and quantitative approaches. Bosnia and Herzegovina in 2000 was selected as an example of a post-conflict, resource-poor country facing typical challenges of a newly created administrative structure, gaps in population health data for child and maternal health, and a destroyed health information system. The complex national context included multiple international agencies with varying mandates and approaches to improving the national HIS. The governance and management model of the BiH MICS 2000 survey successfully addressed the fractured administrative structure in the country. A model for that enabled further national household surveys in BiH was created. The lessons learned in implementing the BiH MICS survey might be useful in other fragile states. The BiH MICS 2000 survey measured 32 internationally agreed indicators in the following health domains: education and literacy, access to clean water and sanitation, child nutrition, childhood immunization, the UNICEF/WHO global programme ‘Integrated Management of Childhood illness’, HIV/AIDS awareness, contraceptive prevalence, orphanhood, and child labour. A lack of socio-economic, ethnic or refugee/displaced information meant that population disparities, beyond urban and rural, could not be elicited from the data. The data provided substantial inputs into the four main national human development monitoring processes in close time proximity to the survey. They were: the National Report on Follow up to the World Summit for Children (2000), the National Action Plan for Children in Bosnia and Herzegovina 2002-2010 (2002), the Bosnia and Herzegovina Human Development Report/Millennium Development Goals 2003, and the Bosnia and Herzegovina Medium Term Development Strategy (2004). Comparison of the 32 indicators from 2000 with measures from 1990, 1995 and 2006 was limited by lack of comparable data from these three time points. A second BiH MICS survey, in 2006, provided the closest comparable indicators. The planned third BiH MICS survey in 2011 will create a unique national resource of information extending over 15-year period. The MICS data is widely presented, however there is currently no set of tools and guidelines for analysis of the MICS data over time. This study acknowledges the useful contribution by the BiH MICS survey indicators to international monitoring of child and maternal health, but not all indicators were relevant for a middle-income country, and the regional and national policy context of BiH was not sufficiently addressed. The survey draws attention to the need for a longer-term and more integrated approach to strengthening health information systems in post-conflict countries. Conducting a standalone household survey can produce data, but a national health information system requires a locally built and designed HIS architecture. Future MICS surveys and other data collection efforts should take into account the aspirations of BiH to join the European Union and the core indicator set being developed and maintained by EuroStat, the statistical office of the European Union.
Keywords: Public Health and Primary Care, M.D.; M.D. Trinity College Dublin